Software reliability modeling for fault detection and fault correction processes considering Burr Type X testing effort function - Kumar, Kaushal; Ahmad, Nesar; Ahmad, Zubair; Kumar, Jitendra (Frontiers in Applied Mathematics and Statistics, 2025)
Software reliability analysis is vital for evaluating software quality, where reliability is the probability of failure operation of a system for a specified duration. Numerous SRGMs have been proposed, mainly based on the NHPP to enhance the reliability of software product. A key aspect of software reliability modeling involves the FDP and FCP, both of which are vital for understanding and predicting software performance. These models have evolved to consider dependencies between FD and FC, time delay effects, and testing effort consumption, thereby refining predictions and providing robust reliability estimates. In this paper, we first provide a comprehensive review of the last four decades of research on software reliability modeling, focusing on methods proposed for predicting software reliability through FDP and FCP. We then present the FDP and FCP for imperfect debugging considering BTXTEF. Two specific paired FDP and FCP models are proposed with BTXTEF. The proposed SRGM with BTXTEF contains some undetermined parameters. We use PSO to optimize these parameters on an actual dataset rather than using traditional estimation methods. We compare the performance of the proposed SRGM model, in relation to other existing models from the literature. The results reveal that the proposed SRGM with BTXTEF for FDP and FCP is highly effective and outperforms existing models.